Quantum chemical interpretation of ultrafast luminescence decay and intersystem crossings in rhenium(I) carbonyl bipyridine complexes - Gourlaouen, Christophe; Eng, Julien; Otsuka, Miho; Gindensperger, Etienne; Daniel, Chantal (Journal of chemical theory and computation, 2015)
Ultrafast luminescence decay and intersystem crossing processes through the seven low-lying singlet and triplet excited states of [Re (X)(CO)3(bpy)] (X = Cl, Br, I; bpy = 2,2'-bipyridine) are interpreted on the basis of time-dependent density functional theory (TD-DFT) electronic structure calculations performed in acetonitrile and including spin-orbit coupling (SOC) effects within the zeroth-order approximation. It is shown that the red shift of the lowest part of the spectra by SOC increases from X = Cl (0.06 eV) to X = Br (0.09 eV) and X = I (0.18 eV) due to the participation of the triplet sublevels to the absorption. The six lowest "spin-orbit" states remain largely triplet in character and the maximum of absorption is not drastically affected by SOC. While the energy of the excited states is affected by SOC, the character of these states is not significantly modified: SOC mixes states of the same nature, namely metal-to-ligand-charge-transfer/halide-to-ligand-charge-transfer (MLCT/XLCT). This mixing can be large, however, as illustrated by the S1/T2 (a(1)A″/a(3)A') mixing that amounts to about 50:50 within the series Cl > Br > I. On the basis of the optimized structures of the six lowest excited states an interpretation of the emission signals detected by ultrafast luminescence spectroscopy is proposed. It is shown that whereas the experimental Stokes shift of 6000 cm(-1) observed for the three complexes is well reproduced without SOC correction for the Cl and Br complexes, SOC effects have to be taken into account for the iodide complex. The early signal of ultrafast luminescence detected immediately after absorption at 400 nm to the S2 state, covering the 500-550 nm energy domain and characterized by a decay τ1 = 85 fs (X = Cl) and 128 fs (X = Br), is attributed to S2 calculated at 505 and 522 nm, respectively, and to some extend to T3 by SOC. The intermediate band observed at longer time-scale between 550 and 600 nm with emissive decay time τ2 = 340 fs (X = Cl) and 470 fs (X = Br) can be assigned to T2 calculated at 558 and 571 nm, respectively. The S1 state could also participate to this band by SOC. In both complexes the long-lived emission at 600-610 nm is attributed to the lowest T1 state calculated at 596 and 592 nm for the chloride and bromide complexes, respectively, and shifted to ∼610 nm by SOC. Important SOC effects characterize the luminescence decay of [Re (I)(CO)3(bpy)], the mechanism of which differs significantly of the one proposed for the two other complexes. The A' spin-orbit sublevel of T3 state calculated at 512 nm with an oscillator strength of 0.17 × 10(-1) participates to the first signal characterized by a rapid decay (τ1 = 152 fs) with a maximum at 525 nm. The intermediate band covering the 550-600 nm region with a decay time τ2 = 1180 fs is assigned to the "spin-orbit" S1 state calculated at 595 nm. The S2 absorbing state calculated at 577 nm could contribute to these two signals. According to the spin-orbit sublevels calculated for T1 and T2, both states contribute to the long-lived emission detected at 600-610 nm, T1 with two sublevels A' of significant oscillator strengths of ∼10(-1) being the main contributor. In order to follow the evolution of the excited states energy and SOC as a function of the Re-X stretching normal mode their potentials have been calculated without and with SOC as a function of the mass and frequency weighted Re-X stretching mode displacement from the Franck-Condon geometries. Exploratory wavepacket propagations show that SOC alone cannot account for the whole ISC process. Vibronic effects should play an important role in the ultrafast luminescence decay observed experimentally.